Should Millions of Students Take a Gap Year? Large Numbers of Students Start the School Year Above Grade Level. (July 2017) - Peters, Scott J.; Rambo-Hernandez, Karen; Makel, Matthew C.; Matthews, Michael S.; Plucker, Jonathan A.
Few topics have garnered more attention in preservice teacher training and educational reform than student diversity and its influence on learning. However, the actual degree of cognitive diversity has yet to be considered regarding instructional implications for advanced learners. We used four data sets (three state-level and one national) from diverse contexts to evaluate how many students perform above grade level in English Language Arts and mathematics. Results revealed that among American elementary and middle school students, 20% to 49% in English Language Arts and 14% to 37% in mathematics scored 1 year or more above grade level. We address what these findings imply for K-12 schools, grouping decisions, and educational policies that strive to foster advanced abilities.